Thermal behaviour of different biomass materials under slow pyrolysis conditions - Simona Domazetovska; Vladimir Strezov; Tao Kan; Risto V. Filkoski (Wojciech Budzianowski Consulting Services, 2017)
The use of carbon neutral renewable sources to achieve reduction in carbon emission, soaring prices of petroleum and concerns over secured supply of energy sources are the major drivers in the search for alternative renewable energy sources. Typical and abundant biomass residues, such as corn cob, vine rod and sunflower have potential to produce energy when subjected to pyrolysis conversion through biogas, bio-oils and bio-char products of pyrolysis. The subject of investigation of this work was to determine the thermal behaviour of these three biomass agricultural materials under slow pyrolysis conditions to quantify their energy content. In this work, a variety of technological tools were employed to characterise the pyrolysis of the three samples. The thermo-gravimetric analyser and proximate analyses were used on the raw samples to monitor the mass change and characterise the samples. The organic compounds contained in the pyrolysis oils at 500˚C were investigated using gas chromatography- mass spectrometry (GC-MS). The solid char products of pyrolysis at 500˚C and the raw samples were analysed using Fourier transform-infrared (FT-IR) spectroscopy. The results indicate change in functional groups between raw and solid char products, which refers to the loss of organics after pyrolysis at 500˚C. Тhe composition in the bio-oil was compared of the selected biomass materials. Through proximate analysis, the calorific value was determined. The obtained data will provide important reference information for energy and fuel generation from pyrolysis of the analysed biomass.
Keywords: : Renewable energy, biomass, biofuel, slow pyrolysis, corn cob, vine rod, sunflower